Accuracy, use and acceptability of the VISITECT CD4 semi-quantitative test to advance HIV disease screening in routine programmatic settings in Tanzania - Frederick Haraka; Ana Moore; Godfrey Odinga; Rebecca Bailey; Juma Songoro; Dennis Haule; Julius Mkumbo; Thomas Machalo; Roland Van de Ven; Sajida Kimambo; Werner Maokola; Anath Rwebembera; et al. (Elsevier, 2024)
Background: The available few laboratory-based CD4 assay for People Living with HIV (PLHIV) experience supply stock-outs and instrument breakdowns in developing countries, affecting the ability to diagnose Advance HIV disease (AHD). We evaluated the performance of the VISITECT CD4 point of care test among healthcare workers in HIV program in Tanzania. Methods: A retrospective diagnostic accuracy study was conducted among PLHIV who received both the VISITECT CD4 and a standard-of-care. Acceptability of the VISITECT CD4 by healthcare workers was assessed using a structured questionnaire. Both FACS Count and Pima CD4 assay were considered as reference standards. Findings were summarized as proportions with 95 % confidence intervals (CI). Data were analyzed using STATA 17 (StataCorp, College Station, TX). Results: A total of 1370 PLHIV were tested using VISITECT CD4 across 20 facilities between 3 April and 14 September 2022. The median age was 37 (Interquartile range (IQR):29-46). Overall, 897 (65.5 %) were females and 449 had both VISITECT CD4 test and standard of care. The sensitivity and specificity were; 95.9 % (95 % CI: 91.8 %-98.3 %) and 78.3 % (95 % CI: 73.0 %-83.0 %) respectively. 47 healthcare workers used the VISITECT CD4, of whom 57.5 % were non-laboratory healthcare workers. Majority of the healthcare workers were of the opinion that the training was adequate and VISITECT CD4 was easy and useful in clinical decisions. Conclusion: The VISITECT CD4 test was accurate, useable and acceptable among healthcare workers in Tanzania. The scale up of VISITECT CD4 should consider development of training curriculum and the use of job aids particularly for non-laboratory healthcare workers.